2018
DOI: 10.1111/dom.13241
|View full text |Cite
|
Sign up to set email alerts
|

Elevations of metabolic risk factors 20 years or more before diagnosis of type 2 diabetes: Experience from the AMORIS study

Abstract: Development of T2D is associated with subtle elevations in glucose and lipid levels >20 years before diagnosis. This suggests that diabetogenic processes tied to chronic insulin resistance operate for decades prior to the development of T2D. A simple risk classification can help in early identification of individuals who are at increased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
9
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
5
9
0
5
Order By: Relevance
“…In individuals hospitalized for MI, impaired glucose metabolism is a common finding, with less than 35% showing normal glucose tolerance [ 25 ]. In a previous study, we found elevation of lipids, lipoproteins, and the apoB/apoA-1 ratio to be present about 15 years before diagnosis of type 2 diabetes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In individuals hospitalized for MI, impaired glucose metabolism is a common finding, with less than 35% showing normal glucose tolerance [ 25 ]. In a previous study, we found elevation of lipids, lipoproteins, and the apoB/apoA-1 ratio to be present about 15 years before diagnosis of type 2 diabetes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Безусловно, ИР служит первым звеном патогенеза СД2. При этом гипергликемия является отдаленным следствием ИР [11], при которой реализуется повреждающее действие ряда молекулярных метаболических нарушений, включая оксидативный и карбонильный стресс клеток-мишеней. Эндотелий сосудов не является классически инсулин-зависимым, но служит первичной мишенью инсулина.…”
unclassified
“…(2018) в специальном анализе 296428 человек из когорты Swedish AMORIS study показали, что в случаях СД2 отмечались более высокие показатели ИМТ и уровни глюкозы плазмы натощак (ГПН) и ТГ по сравнению с контролем более, чем за 20 лет до постановки диагноза. То есть, диабетогенные процессы, связанные с ИР, действуют десятилетиями до развития СД [11]. При выборке из когорты AMORIS пациентов моложе 50 лет, оказалось, что около 50% больших сердечно-сосудистых событий (ССС) в этом возрасте могут быть связаны с повышенным уровнем липидов и глюкозы крови [26].…”
unclassified
See 1 more Smart Citation
“…Безусловно, она служит первым звеном патогенеза НУО с их прогрессированием в СД2. При этом гипергликемия является отдаленным следствием ИР [12], при которой реализуется повреждающее действие ряда молекулярных метаболических нарушений, включая оксидативный и карбонильный стресс клеток-мишеней. Эндотелий сосудов не является классически инсулинзависимым, но служит первичной мишенью инсулина.…”
unclassified